2014
DOI: 10.1063/1.4901646
|View full text |Cite
|
Sign up to set email alerts
|

Local rhombohedral symmetry in Tb0.3Dy0.7Fe2 near the morphotropic phase boundary

Abstract: The recently reported morphotropic phase boundary (MPB) in a number of giant magnetostrictive materials (GMMs) has drawn considerable interest to the local symmetry/structure near MPB region of these materials. In this letter, by in-situ X-ray diffraction and AC magnetic susceptibility measurements, we show that Tb0.3Dy0.7Fe2, the typical composition of Terfenol-D GMMs, has coexistence of rhombohedral and tetragonal phases over a wide temperature range in the vicinity of MPB. High resolution transmission elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In addition, this local rhombohedral symmetry was further proved by high-resolution transmission electron microscopy. The local nanodomains of ferromagnetic rhombohedral and tetragonal phases coexist in Tb 0.3 Dy 0.7 Fe 2 , as shown in Figure 16 [74]. This is similar to the hierarchical nanodomain structure in ferroelectric materials.…”
Section: Structural Origin and Magnetic Morphotropic Phase Boundary (...supporting
confidence: 63%
“…In addition, this local rhombohedral symmetry was further proved by high-resolution transmission electron microscopy. The local nanodomains of ferromagnetic rhombohedral and tetragonal phases coexist in Tb 0.3 Dy 0.7 Fe 2 , as shown in Figure 16 [74]. This is similar to the hierarchical nanodomain structure in ferroelectric materials.…”
Section: Structural Origin and Magnetic Morphotropic Phase Boundary (...supporting
confidence: 63%
“…29)), Nd–Fe–B (the strongest permanent magnet, T C ∼585 K), and Fe–Co–V ( T C ∼1,014 K) commercial magnets. The solution-treated sample (black curve) suffers gradual magnetization deterioration upon heating to ∼700 K, which is similar to normal Curie transition.…”
Section: Resultsmentioning
confidence: 99%
“…The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/crat.202100246 DOI: 10.1002/crat.202100246 Some recent works report that the breaking of the local symmetry in nanoscale leads to large magnetostrictive response. [11,12] The effect of local composition distribution on the magnetostrictive effect in Fe-Ga systems was also revealed by theoretical studies. [13,14] These works highlight the important role of the local structure in determining the magnetostrictive properties.…”
Section: Introductionmentioning
confidence: 88%
“…However, the detailed information of the local structure of RT 2 compounds is still rare. Ma et al [11] reported the local rhombohedral symmetry near the morphotropic phase boundary in Tb 0.3 Dy 0.7 Fe 2 . Recently, Chang et al studied the local structure of the Tb 0.4 Dy 0.6 Fe 2 and reported that the evolution of the local structure is different from the average structure.…”
Section: Introductionmentioning
confidence: 99%